(untitled) (Asean Journal of Engineering Education, 2024)
A proper design of the Competency-Based Learning (CBL) teaching and learning (T&L) environment is crucial for attaining the desired learning outcomes (DLOs), by chemical engineering students. This paper aims to analyze the successful practices of implementing common CBL elements into the existing OBE, ABET-accredited, chemical engineering curriculum, without disturbing the logistics of the current engineering programs. The paper describes and analyzes the implementation of a CBL environment in teaching thermodynamics, as an example of typical chemical engineering courses, at Higher Colleges of Technology (HCT), United Arab Emirates (UAE). The analysis considered teaching thermodynamics after and before CBL implementation, during the 2023-24 and 2022-23 academic years, respectively. The process included scaffolding steps necessary for engineering students to attain DLOs. In addition, the process may serve as a metric for educators in CBL implementation across other engineering courses.